GAMMA STRENGTH FUNCTION OF 49Ti BASED ON (n, 2γ) REACTION - Nguyễn Đức Hòa (Tạp chí Khoa học Đại học Đà Lạt)
Gamma strength functions are important information to study nuclear structure by experiment. The experimental data will check the correctness of the nuclear structure models theory. Nowadays, the comparison between experiment and theory of gamma strength function is two to four order differences. This report presents some measurement results of gamma strength function which is based on 48Ti(n, 2γ)49Ti reaction